Review of the pyrolysis platform for coproducing bio-oil and biochar - Laird, David A.; Brown, Robert C.; Amonette, James E.; Lehmann, Johannes (Biofuels, bioproducts and biorefining, 2009)
Pyrolysis is a relatively simple, inexpensive, and robust thermochemical technology for transforming biomass into bio‐oil, biochar, and syngas. The robust nature of the pyrolysis technology, which allows considerable flexibility in both the type and quality of the biomass feedstock, combined with a distributed network of small pyrolysis plants, would be compatible with existing agriculture and forestry infrastructure. Bio‐oil can be used as a fuel in existing industrial boilers. Biochar can be used with existing infrastructure as a replacement for pulverized coal; however, use of biochar as a soil amendment results in significant environmental and agronomic benefits. Soil application of biochar is a means of sequestering large amounts of C and may have other greenhouse gas benefits. Preliminary reports of the impact of soil biochar applications on crop yields indicate that biochar quality is very important. Biochar is an effective adsorbent for both nutrients and organic contaminants, hence the presence of biochar in soils has been shown to improve water quality in column leaching and field lysimeters studies and it is anticipated to do the same for agricultural watersheds. The pyrolysis platform for producing bio‐oil and biochar from biomass appears to be a practical, effective, and environmentally sustainable means of producing large quantities of renewable bioenergy while simultaneously reducing emissions of greenhouse gases. At the present time, the pyrolysis platform is economically marginal because markets for bio‐oil and biochar are highly competitive. However, if the USA adopts a program for controlling greenhouse gases, the pyrolysis platform would be highly competitive. Published in 2009 by John Wiley & Sons, Ltd